PsycEXTRA Dataset 2000
DOI: 10.1037/e453712006-001
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Self-Reported Injuries Among Special Boat Operators

Abstract: Special Operations place great physical demands on personnel. In most Navy settings, greater physical demands are associated with greater musculoskeletal injury rates. Within the Special Operations community, Special Boat operators have a unique set of risks. Small boats operating in the open ocean are subject to large shock and vibration forces. Exposure to such forces can lead to discomfort, injury and performance degradation. In an effort to begin assessing the prevalence of injuries related to operations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 2 publications
0
29
0
Order By: Relevance
“…Epidemiological data from large military populations indicate that low back pain (LBP) is the most frequent diagnosis for individuals deployed during Operation Iraqi Freedom 5 as well as individuals who were not deployed. 19 Although SFOs suffer a wide distribution of joint injuries, 10 , 24 , 34 epidemiological evidence, including our own data, have demonstrated that the lumbar spine is 1 of the 3 most common locations for musculoskeletal injuries. 34 , 42 …”
mentioning
confidence: 84%
“…Epidemiological data from large military populations indicate that low back pain (LBP) is the most frequent diagnosis for individuals deployed during Operation Iraqi Freedom 5 as well as individuals who were not deployed. 19 Although SFOs suffer a wide distribution of joint injuries, 10 , 24 , 34 epidemiological evidence, including our own data, have demonstrated that the lumbar spine is 1 of the 3 most common locations for musculoskeletal injuries. 34 , 42 …”
mentioning
confidence: 84%
“…With the increasing speed of RIBs there have been anecdotal reports of embarked personnel suffering from reductions in physical performance post-transit and chronic musculoskeletal injury. The existence of the latter is supported by US Navy and US Coastguard data for injury rates (Carvalhais 2004;Ensign et al 2000) and reports of back injuries in military operators (Smith 2007). The seating and ergonomics onboard open HSC are often poor (Dobbins 2004), with passengers having a restricted view of oncoming waves and the ability to anticipate impacts, especially at night.…”
Section: Introductionmentioning
confidence: 90%
“…Physiological injuries have been reported by Ensign et al (2000) to include; spinal and abdominal injuries, damage to internal organs (kidneys), torn ligaments and, broken ankles and legs. Ensign et al (2000) also reported that the psychological injuries include; annoyance, fatigue, anxiety, loss of visual accuracy and reduced hand-eye coordination (the latter two could be considered a combination of both physiological and psychological effects). Myers et al (2011) demonstrated a three hour transit at 40 knot in HSC will reduce the physical performance of the crew (including run distance and vertical jump height).…”
Section: Introductionmentioning
confidence: 99%